2020
DOI: 10.2196/18127
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Training Using Fully Immersive, Enriched Environment Virtual Reality for Patients With Mild Cognitive Impairment and Mild Dementia: Feasibility and Usability Study

Abstract: Background Cognitive training using virtual reality (VR) may result in motivational and playful training for patients with mild cognitive impairment and mild dementia. Fully immersive VR sets patients free from external interference and thus encourages patients with cognitive impairment to maintain selective attention. The enriched environment, which refers to a rich and stimulating environment, has a positive effect on cognitive function and mood. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 30 publications
(33 reference statements)
3
35
0
3
Order By: Relevance
“…We observed that owing to the visual content and interaction style through VR, most subjects found the task more interesting than traditional screening tools and were more willing to take the test. Yun et al [ 46 ] also reported elderly people's interest in VR. Implementation studies are needed in the future to evaluate its rollout in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that owing to the visual content and interaction style through VR, most subjects found the task more interesting than traditional screening tools and were more willing to take the test. Yun et al [ 46 ] also reported elderly people's interest in VR. Implementation studies are needed in the future to evaluate its rollout in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 presents relevant studies [3,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] related to the use of digital solutions to support physical activities or cognitive and physical activities with different purposes (i.e., postural control and prevention of falls [51,53,54,58,59,65], assistance in physical exercises [52,56,61], physical activity adherence [55], improvement of physical performance [58][59][60]63,64], and improvement of cognitive performance [3,57,60,62,64]). The studies are supported in various types of technologies, namely exergames and virtual reality [51,53,54,[57][58][59][60][61][62][63]…”
Section: Related Workmentioning
confidence: 99%
“…The studies are supported in various types of technologies, namely exergames and virtual reality [51,53,54,[57][58][59][60][61][62][63]65], robotics [52,56,61], and mobile devices [3]. In turn, some of these articles report interactions mechanisms based on the recognition of body movements (e.g., using Kinect [51,52,57,58,65], Nintendo Wii Fit [53], or wearable devices [59,60]), feet movements using step training platforms [54,63], or leg movements on a training bicycle [55]. When compared with stat-of-the-art technological solutions, the study reported by this article presents two important advantages: (i) support tools and clinical information integration and (ii) automatic quantification of patient's cognitive performance during dual-task training.…”
Section: Related Workmentioning
confidence: 99%
“…Yun et al (24) realizaron una intervención con 4 juegos de cosecha y 3 de cocina con 11 pacientes con demencia y deterioro cognitivo leve en una sesión única de 30 minutos. Aplicaron las escalas MMSE y CDR, y analizaron las variables viabilidad, usabilidad, tiempo de reacción y velocidad motora.…”
Section: (Media)unclassified